Altitude and COVID-19: Friend or foe? A narrative review - Millet, G. P.; Debevec, T.; Brocherie, F.; Burtscher, M.; Burtscher, J. (Physiological Reports, 2021)
Recent reports suggest that high-altitude residence may be beneficial in the novel coronavirus disease (COVID-19) implicating that traveling to high places or using hypoxic conditioning thus could be favorable as well. Physiological high-altitude characteristics and symptoms of altitude illnesses furthermore seem similar to several pathologies associated with COVID-19. As a consequence, high altitude and hypoxia research and related clinical practices are discussed for potential applications in COVID-19 prevention and treatment. We summarize the currently available evidence on the relationship between altitude/hypoxia conditions and COVID-19 epidemiology and pathophysiology. The potential for treatment strategies used for altitude illnesses is evaluated. Symptomatic overlaps in the pathophysiology of COVID-19 induced ARDS and high altitude illnesses (i.e., hypoxemia, dyspnea…) have been reported but are also common to other pathologies (i.e., heart failure, pulmonary embolism, COPD…). Most treatments of altitude illnesses have limited value and may even be detrimental in COVID-19. Some may be efficient, potentially the corticosteroid dexamethasone. Physiological adaptations to altitude/hypoxia can exert diverse effects, depending on the constitution of the target individual and the hypoxic dose. In healthy individuals, they may optimize oxygen supply and increase mitochondrial, antioxidant, and immune system function. It is highly debated if these physiological responses to hypoxia overlap in many instances with SARS-CoV-2 infection and may exert preventive effects under very specific conditions. The temporal overlap of SARS-CoV-2 infection and exposure to altitude/hypoxia may be detrimental. No evidence-based knowledge is presently available on whether and how altitude/hypoxia may prevent, treat or aggravate COVID-19. The reported lower incidence and mortality of COVID-19 in high-altitude places remain to be confirmed. High-altitude illnesses and COVID-19 pathologies exhibit clear pathophysiological differences. While potentially effective as a prophylactic measure, altitude/hypoxia is likely associated with elevated risks for patients with COVID-19. Altogether, the different points discussed in this review are of possibly some relevance for individuals who aim to reach high-altitude areas. However, due to the ever-changing state of understanding of COVID-19, all points discussed in this review may be out of date at the time of its publication.